Association Between Healthy Diet and Exercise and Greater Muscle Mass in Older Adults. Issue 5 (27th April 2015) - Kim, Jinhee; Lee, Yunhwan; Kye, Seunghee; Chung, Yoon‐Sok; Kim, Kwang‐Min
<x xml:space="preserve">Abstract</x> Objectives To examine the association between healthy diet and exercise, individually and combined, and low muscle mass in older Korean adults. Design Population‐based cross‐sectional study from the Fourth and Fifth Korea National Health and Nutrition Examination Surveys from 2008 to 2011. Setting Community. Participants Nationally representative sample aged 65 and older (1, 486 men, 1, 799 women) in the Republic of Korea. Measurements A food frequency questionnaire was used to determine frequency of food group consumption (meat, fish, eggs, legumes; vegetables; fruits). Participation in exercise (aerobic and resistance) was based on self‐report. Combined healthy lifestyle factors were calculated as the number of recommendations met regarding consumption of food groups and exercise performed. Appendicular skeletal muscle mass (ASM) was measured using dual‐energy X‐ray absorptiometry, and low muscle mass was defined using the variable of ASM adjusted for weight. Logistic regression analysis was performed to examine the association between healthy lifestyle factors and low muscle mass, adjusting for sociodemographic characteristics and health‐related variables. Results In women, after controlling for covariates, vegetable consumption (odds ratio (OR) = 0.52, 95% confidence interval (CI) = 0.30–0.89) and aerobic exercise (OR = 0.62, 95% CI = 0.39–1.00) were inversely associated with low muscle mass. Also, the odds of low muscle mass was lower in women with three or more healthy lifestyle factors versus none (OR = 0.45, 95% CI = 0.23–0.87). In men, there were no associations between food group consumption and exercise and low muscle mass. Conclusion Older women who exercise and consume a healthy diet have lower odds of low muscle mass. Engaging in multiple healthy behaviors may be important in preventing low muscle mass in late life.